The Codetermination of the Andean Social Organization - Golte, Jürgen (1983)
Andean communities appear to us as dynamic groups that allow the reproduction of their parts, that is: domestic units, extended families, ayllus, neighborhoods, etc. These groups are not isolated, but are inserted into regional economies and are linked to both the national market and the world market. These markets have specific historical characteristics, of which perhaps the most important is their generalizing potential, fundamentally due to the way in which values ​​are assigned to each of the factors of the production process that are understood as universally interchangeable, that is, as merchandise